The Impact of Intracerebral Hemorrhage on the Progression of White Matter Hyperintensity - Chen, Xuemei; Chen, Xin; Chen, Yan; Xu, Manman; Yu, Tingting; Li, Junrong (Frontiers in Human Neuroscience, 2018)
OBJECTIVE: The exact relationship between white matter hyperintensity (WMH) and intracerebral hemorrhage (ICH) after ICH remains unclear. In this retrospective study, we investigated whether patients with ICH had more severe WMH progression. PATIENTS AND METHODS: A total of 2951 patients aged ≥ 40 years with ICH who received brain computed tomography (CT) imaging within 12 hours of ICH symptom onset were screened. Ninety patients with two fluid-attenuated inversion recovery (FLAIR) magnetic resonance imaging (MRI) assessments, including 36 patients with Lobar ICH, 40 with basal ganglia region ICH, and 14 with ICH at other sites, were included in the final study. We selected 90 age- and gender-matched healthy individuals with two MRI scans as the control group. The WMH volume at baseline and follow-up was assessed using the FLAIR image by MRICRON and ITK-SNAP software, while the hematoma volumes were calculated based on the CT images using ITK-SNAP software. RESULTS: The annual progression rate of WMH was significantly higher in the ICH group compared with the control group (p<0.05). Furthermore, WMH progression was associated with the ICH volume. The largest ICH volume (>30 mL)was associated with the highest annual progression rate of WMH (p<0.05). In contrast, no trend toward an association between ICH location and the annual progression rate of WMH was observed (p>0.05). CONCLUSIONS: Our results showed that ICH patients had more severe WMH progression and that larger ICH volume was related to greater progression of WMH after ICH. These results could provide important prognostic information about patients with ICH.